Sesame an ancient oilseed in 21st century, routing hunger and malnutrition - Sharma, Chandrika; Naberia, Seema (Indian Farming, 2018)
Sesame can be taken by small farmers with low inputs not only to overcome hunger and malnutrition but also to gain good market prices through practicing above recommended practices.